Financement des entreprises en Afrique : Repenser l'action des institutions financières de développement - Florian Léon (Fondation pour les études et recherches sur le développement international (FERDI), 2025)
– In Africa, small and medium-sized enterprises (SMEs) face a chronic financing gap that hinders their growth and the continent's economic development. Development Finance Institutions (DFIs) are often seen as a solution to bridge this gap, particularly through indirect support to local banks. However, an in-depth analysis of their impact reveals mixed results. While targeted beneficiaries benefit from these programs, it is at the expense of other borrowers. There is a need to rethink the support for these DFI-intermediated financing schemes aimed at supporting the SME sector.
Keywords: 330; Afrique; Banques